ANALISIS TERJEMAHAN MAKNA INTERPERSONAL DALAM DUBBING FILM THOMAS AND FRIENDS: BLUE MOUNTAIN MYSTERY - Anggororeni, Pramesty; Santosa, Riyadi; Wiratno, Tri (LINGUA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
This reasearch aims to describe translation qualities of proposal clause, explain the effect of translation techniques to the translation qualities and Â the impact of proposal translations to the children as target viewer on dubbing interpersonal-transacsional: proposal â€œThomas and Friends: Blue Mountain Mysteryâ€ the movie. This descriptive-qualitative research applies purposive sampling techniques. The main resource is dubbing â€œThomas and Friends: Blue Mountain Mysteryâ€ the movie and its indonesian version. Data were collected using: (1) document analysis to obtain the clause of interpersonal-transacsional: proposal, (2) questionnaire and interview to obtain translation quality data which covers accuracy, acceptability and readability. The result of the study shows that movie dubbing used narrative genre and its text structure is devided into orientation, complication and resolution. Each structure consists of declarative clause, interogative and imperative. The translation shifts occured in the forms of declarative clause and imperative clause. The shift types are in the clause type, proposal meaning or social function, and in both clause type and meaning.Â